AUDIT DELAY IN FOOD AND BEVERAGE FIRMS: SIZE, PROFITABILITY, AND AUDITOR REPUTATION - Yuniarti, Rita (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2026)
Audit delay refers to the time lag in the issuance of audited financial statements, which can reduce the relevance of information for users. This study examines the effect of firm size, return on assets (ROA), and audit firm reputation on audit delay in manufacturing companies within the food and beverage subsector listed on the Indonesia Stock Exchange during 2019–2023. A quantitative approach with a causal design was applied. Using purposive sampling, 26 companies were selected from a population of 30 firms, resulting in 130 observations. Data were analyzed using SPSS version 27. The findings show that ROA has a negative and significant effect on audit delay, indicating that more profitable companies tend to complete audits faster. In contrast, firm size and audit firm reputation do not significantly influence audit delay. These results suggest that audit timeliness is driven more by financial performance than by company scale or auditor affiliation. This study provides empirical evidence on audit delay determinants and offers insights for management, auditors, investors, and regulators to improve the timeliness of audited financial reporting.